2022
DOI: 10.3390/vaccines10071155
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine for Children: Vaccination Willingness of Parents and Its Associated Factors—A Network Analysis

Abstract: Different COVID-19 vaccines have been approved for underage children, so parents and caregivers currently face the decision of whether to vaccinate their children against COVID-19 or not. Due to the rather moderate vaccine acceptance among parents across different countries, the objective of the present study was to investigate the relationship between different psychological, demographic, and behavioral factors related to the acceptance of the COVID-19 vaccine for underage children among parents. In particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 72 publications
4
9
0
Order By: Relevance
“…Furthermore, previous results indicated that parents who were COVID-19 immunized were also willing for their children to receive the vaccine. This finding is consistent with other results in the literature [ 25 , 26 , 36 , 57 , 58 ]. Fittingly, there was a very strong positive correlation between parents’ perceived importance of vaccination as protection against other infections and the COVID-19 vaccination willingness ( r = 0.734; p adj < 0.05).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Furthermore, previous results indicated that parents who were COVID-19 immunized were also willing for their children to receive the vaccine. This finding is consistent with other results in the literature [ 25 , 26 , 36 , 57 , 58 ]. Fittingly, there was a very strong positive correlation between parents’ perceived importance of vaccination as protection against other infections and the COVID-19 vaccination willingness ( r = 0.734; p adj < 0.05).…”
Section: Discussionsupporting
confidence: 94%
“…Except for gender, residence area, DT, and PHQ-8, all determinants showed significant associations with vaccination willingness in this study. In line with previous research, significant correlations were exhibited between vaccination willingness and educational level, marital status, and age [ 25 , 26 , 36 , 47 , 48 ]. The correlation between age and COVID-19 vaccination willingness was found to be moderate ( r = 0.208; p adj < 0.05).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, being aware that COVID-19 was a severe disease predicts all three outcomes of interest. This is not surprising, since the individual beliefs about COVID-19 disease surely influence the attitude and the decision to get the vaccine as observed in several previous studies from Western countries [33][34][35][36][37][38][39][40][41][42]. It should be noted that another key finding was the influence of a higher self-awareness of the risk of infection on a higher perception of the utility of the second booster dose [19,23].…”
Section: Discussionmentioning
confidence: 52%